De‐extinction and evolution. (30th August 2016) - Robert, Alexandre; Thévenin, Charles; Princé, Karine; Sarrazin, François; Clavel, Joanne
Summary: De‐extinction, the process of resurrecting extinct species, is in an early stage of scientific implementation. However, its potential to contribute effectively to biodiversity conservation remains unexplored, especially from an evolutionary perspective. We review and discuss the application of the existing evolutionary conservation framework to potential de‐extinction projects. We aim to understand how evolutionary processes can influence the dynamics of resurrected populations and to place de‐extinction within micro‐ and macro‐evolutionary conservation perspectives. In programmes aiming to revive long‐extinct species, the most important constraints to the short‐term viability of any resurrected population are (i) their intrinsically low evolutionary resilience and (ii) their poor eco‐evolutionary experience, in relation to the absence of (co)adaption to biotic and abiotic changes in the recipient environment. Assuming that some populations of resurrected species can persist locally, they have the potential to bring substantial benefits to biodiversity if the time since initial extinction is short relative to evolutionary dynamics. The restoration of lost genetic information could lead, along with the reinstatement of lost ecological functions, to the restoration of some evolutionary patrimony and processes, such as adaptation and diversification. However, substantial evolutionary costs might occur, including unintended eco‐evolutionary changes in the local system and unintended spread of the species. Further, evolutionary benefits are limited because (i) the use of resurrected populations as 'evolutionary proxies' of extinct species is meaningless; (ii) their phylogenetic originality is likely to be limited by the selection of inappropriate candidate species and the fact that the original species might be those for which de‐extinction is the most difficult to achieve practically; (iii) the resurrection of a few extinct species does not have the potential to conserve as much evolutionary history as traditional conservation strategies, such as the reduction of ongoing species declines and extinction debts. De‐extinction is a stimulating idea, which is not intrinsically antagonistic to the conservation of evolutionary processes. However, poor choice of candidate species, and most importantly, too long time scales between a species' extinction and its resurrection are associated with low expected evolutionary benefits and likely unacceptable eco‐evolutionary risks. A lay summary is available for this article. Abstract : Lay Summary